SOCIO-ECONOMIC PREREQUISITES AND DEVELOPMENT FACTORS OF DIGITAL TRANSFORMATION OF THE ECONOMY - GOLOBORODKO, Alona (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the main prerequisites and factors of the development of digital transformations of the economy. Digitization has become an integral and important component of the functioning of a civilized society and the main link in the system of development and efficiency of social and economic activities of enterprises. Digital transformations are due to the development of the information society and cover all spheres of life: technical, social, economic, political, cultural. The digital economy has developed as a result of the global transformation of organizations and communications systems and the transition of an industrial society to a digital one. Two main approaches to digital transformations, namely evolutionary and revolutionary, are highlighted and characterized in the study. The study of the features of evolution and features of qualitative and quantitative changes in the system of socio-economic relations made it possible to identify four main stages of digital transformations in the world. Based on the study of the peculiarities of the evolution of digital transformations, the author highlights the main factors of the development of the digital economy in the article. Namely, digital finance, social networks, digital identification and cyber security, large volumes of data and mobility to access them, integration of several management systems and organization of economic activity, the possibility of collaboration in conducting offline and online business. Digital transformations are the result of building a model of interaction of all participants in socio-economic processes and the transition of society and states to a new high-quality level of consumption and provision of products, organization of flow processes and construction of the entire system of economic activity. Based on the established signs of digital transformations in socio-economic processes, the article reveals the components of the digital economy - supporting infrastructure, e-business, e-commerce, resource provision and digital governance.
Keywords: prerequisites; factors; digital transformations; digital economy